Central retinal vein occlusion resulting from anomalous retinal vascular anatomy in a 24-year-old man - Kavoussi SC (Dove Medical Press, 2015)
Shaheen C Kavoussi, James E Kempton, John J Huang Yale University Department of Ophthalmology and Visual Science, New Haven, CT, USA Abstract: An otherwise healthy 24-year-old man presented with a painless decrease of vision in the left eye for 2 days. Best-corrected visual acuity was 20/20 in the right eye and 20/80 in the left eye. Anterior exam was unremarkable and funduscopic exam in the left eye revealed retinal hemorrhages in all four quadrants with venous dilation and tortuosity consistent with central retinal vein occlusion. Fluorescein angiography revealed delayed venous filling with neither leakage nor vasculitis. A comprehensive work-up that included infectious, inflammatory, and hypercoagulability studies was unremarkable, and magnetic resonance imaging of the orbits was unrevealing. After 2 months, best-corrected visual acuity returned to 20/20-2 in the left eye. Upon closer review of the vascular anatomy in the left eye, a bifurcation of the central retinal artery at the level of the optic disc was tightly intertwined with an undilated nasal retinal vein in a manner that appeared to compress the underlying central retinal vein, resulting in dilation and tortuosity of the remaining venous branches. The vessel wall damage, turbulent venous flow, and compressive mass effect resulting from the anomalous retinal vasculature relationship is the proposed mechanism of the central retinal vein occlusion. Careful attention to the retinal vascular anatomy is suggested to aid in assessing the risk of retinal vein occlusion in any age group. Keywords: CRVO, young patient, negative work-up, retinal vascular anatomy